New insights into therapeutic applications and nanoformulation approaches of hesperidin: An updated review - Keshav Bansal; Hemant Bhati; Vanshita; Meenakshi Bajpai (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Hesperidin is a flavanone glycoside occurring in high levels in citrus species. It is among the most significant natural anti-oxidants employed often in pharmaceuticals for therapeutic applications due to its preventive characteristics against inflammation and oxidants. Because of the low hydrophilic properties and poor absorption of hesperidin, appropriate therapeutic effects may not be achieved. Several new viewpoints have been established and proposed to address these issues. Amidst various outlooks, nano carriers-based delivery system has drawn interest and demonstrated a number of benefits in the administration of hydrophobic agents like hesperidin. Methods: Literature was collected from various databases including PubMed, Scopus, Embase, Google Scholar by using keywords including “hesperidin” or “flavonoids” in combination with “Traditional Chinese medicine”, “Therapeutic potential”, “Anti-cancer”, “Neuroprotection”, “Cardio protection”, “Anti-ulcer”, “Anti-aging”, “Nanocarriers”, or “Liposomes”. All the relevant English papers from the years 1989 to 2023 within pertinent peer-reviewed journals were utilized. Results: The present article comprises of recent studies on pharmacological activities of hesperidin. In addition, various nanoformulations developed in the last decade for the delivery of hesperidin has been discussed. Until now, numerous nanocarriers including polymeric nanoparticles, solid lipid nanoparticles, phytosomes, liposomes, nanofibers, nanoemulsions, and hydrogels have been developed that improves the solubility and absorption and provides sustained and controlled release of hesperidin. Conclusion: Nanostructured particles offer several advantages in solving hitches including limited bioavailability as well as stability of hesperidin by overcoming the biological barriers. Certainly, the utilization of herbal nano-drug delivery carriers is undoubtedly the trend. Moreover, the clinical utilization of these nanoformulations needs to be investigated in humans. Such exploration as well as thorough analysis and dose optimization can open up the opportunities for commercial viability of hesperidin.